THE RELATIONSHIP BETWEEN PARENTING PARENTS WITH VIOLENCE EXPERIENCED BY CHILDREN IN ELEMENTARY SCHOOL PANGGANG I GUNUNGKIDUL YOGYAKARTA - Suci Musvita Ayu (Jurnal Kesehatan Masyarakat Indonesia, 2023)
Background: Many parents consider child abuse is normal. They think violence is part of disciplining children. They forget that the parent is the person most responsible for seeking the welfare, protection, increased survival, and optimize their children's growth. Results of a preliminary study conducted on 15 students elementary school district Gunung Panggang I Gunungkidul obtained the data as many as seven children experienced physical abuse by parents by being hit, and as many as eight children experienced psychological violence by getting a rant by a parent.Objective: The purpose of this study was to determine the relationship between parenting parents with violence experienced by children in elementary school Panggang I Gunungkidul Yogyakarta.Methods: This study was an analytic obsevational with cross sectional study design. Determination of the number of samples in this study in proportion to random sampling, the number of samples in this study were 63 respondents. Data collection techniques used in this study was a questionnaire. Data analysistechnique used is the analysis of univariate and bivariate analysis.Results: Parenting was applied parents dominated democratic parenting to 49 children (77.8%). The incidence of child abuse in elementary Panggang I Gunungkidul by parents is dominated by low hardness category were 51 cases (81.0%). Low incidence of violence dominated in applying democratic parenting of the 45 children (71.4%). Further bivariate test results obtained value of research data Exact. Sig. (2-sided) of 0.000 <0.05.Conclusion: There was a relationship between parenting by parents with children experienced violence in elementary school I Panggang Gunungkidul. Keywords: parenting, violence, student.